The Influence Of Job Insecurity And Affective Commitment On Employees’ Intention To Leave - Arifan, Nadzirah (2022)
The purpose of this research is to investigate the component of cognitive, affective, and behavior towards employee intention leave in oil and gas sector in Malaysia. All components in each variable which is cognitive (job insecurity), affective (organizational commitment), behavior (intention to leave) as well as moderator (archetypes of employee responses) have been explored in order to examine the relationship towards intention to leave. The survey was participated by 215 white collar respondents who works in various departments in oil and gas sector in Malaysia. Essentially, this research framework has been built exclusively from cognitive, affective and behavioral model. The data collected have been distributed through online and offline distribution method like Google Form, Email and face to face distribution. The result has been analyzed and examined through Smart PLS statistical tools. The outcomes portray that all components in the variable were significantly related to intention to leave. Affective components which is organizational commitment was justified to mediate the relationship between cognitive components (job insecurity) and behavioral component (intention to leave). The moderators components which is cynical, fearful, hopeful and obliging do moderates the relationship between job insecurity and organizational commitment with t value of 2.246, 2.166, 2.188 and 2.178 respectively. This study is significant and it may assist the oil and gas industry sector to retain its employees simultaneously helping the sector to remain competitive in the industry.